Improved Less Invasive Surfactant Administration Success in Preterm Infants after Procedure Standardization - Björn Liebers; Chinedu Ulrich Ebenebe; Monika Wolf; Martin Ernst Blohm; Eik Vettorazzi; Dominique Singer; Philipp Deindl (MDPI AG, 2021)
Less invasive surfactant administration (LISA) has been introduced at our tertiary Level IV perinatal center since 2016 with an unsatisfactory success rate, which we attributed to an inconsistent, non-standardized approach and ambiguous patient inclusion criteria. This study aimed to improve the LISA success rate to at least 75% within 12 months by implementing a highly standardized LISA approach combined with team training. The Plan Do Study Act method of quality improvement was used for this initiative. Baseline assessment included a review of patient medical records 12 months before the intervention regarding patient characteristics, method success rate, respiratory, and adverse outcomes. A multi-professional team developed a standardized LISA approach and a training program including an educational film, checklists, pocket cards, and team briefings. Twenty-one preterm infants received LISA before and 24 after the intervention. The mean LISA success rate improved from 62% before the intervention to 92% (p = 0.029) after the intervention. Implementing a highly standardized LISA approach and multi-professional team training significantly improved the methods' success rate.